A PRESENCE OF A SUBSTANCE BINDING WITH THE SPECIFIC ANTIBODY AGAINST DOMOIC ACID IN THE THORNY OYSTER SPONDYLUS VERSICOLOR - Ha, Dao Viet (Vietnam Journal of Marine Science and Technology, 2014)
Domoic acid (DA) extracts from 10 specimens of a thorny oyster, Spondylus versicolor collected at Nha Phu bay, Khanh Hoa province, Vietnam in August, 2010 was analyzed individually by High Performance Liquid Chromatography (HPLC) and Indirect Enzyme Linked Immunosorbent Assay (ELISA). Domoic acid levels in the extracts detected by ELISA were always higher than those by HPLC, significantly. In the HPLC chromatogram, the peak of an unknown compound with retention time very close to DA, but different from the known DA isomers was always observed. This substance reacted well with DA-specific antibody in Western Blot experiment, but not corresponding to any standard protein. Our result indicates the occurrence of a certain non-protein substance, which was co-presented with DA in S. versicolor. Further investigation on chemical feature of this substance is under progress.